High-pressure adsorptive storage of hydrogen in MIL-101 (Cr) and AX-21 for mobile applications: Cryocharging and cryokinetics. (5th January 2016) - Bimbo, Nuno; Xu, Wesley; Sharpe, Jessica E.; Ting, Valeska P.; Mays, Timothy J.
Abstract: Current state-of-the-art methods consist of containing high-pressure compressed hydrogen in composite cylinders, with solid-state hydrogen storage materials an alternative that could improve on storage performance by enhancing volumetric densities. A new strategy that uses cryogenic temperatures to load hydrogen (cryocharging) is proposed and analysed in this work, comparing densities and final storage pressures for empty cylinders and containers with the high-surface area materials MIL-101 (Cr) and AX-21. Results show cryocharging as a viable option, as it can substantially lower the charging (at 77 K) and final pressures (at 298 K) for the majority of the cases considered. Kinetics are an equally important requirement for hydrogen storage systems, so the effective diffusivities at these conditions for both materials were calculated, and showed values comparable to the ones estimated in metal–organic frameworks and zeolites from quasielastic neutron scattering and molecular simulations. High-surface area materials tailored for hydrogen storage are a promising route for storage in mobile applications and results show that cryocharging is a promising strategy for hydrogen storage systems, since it increases volumetric densities and avoids energy penalties of operating at high pressures and/or low temperatures. Graphical abstract: Highlights: Cryocharging was shown to be viable for some scenarios in MIL-101 (Cr) and AX-21 Working capacities for MIL-101 (Cr) and AX-21 show low volumetric densities. Diffusivities in MIL-101 (Cr) and AX-21 were found to be comparable to other microporous materials